6(1-2n)=-2(n-2)

Simple and best practice solution for 6(1-2n)=-2(n-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(1-2n)=-2(n-2) equation:


Simplifying
6(1 + -2n) = -2(n + -2)
(1 * 6 + -2n * 6) = -2(n + -2)
(6 + -12n) = -2(n + -2)

Reorder the terms:
6 + -12n = -2(-2 + n)
6 + -12n = (-2 * -2 + n * -2)
6 + -12n = (4 + -2n)

Solving
6 + -12n = 4 + -2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2n' to each side of the equation.
6 + -12n + 2n = 4 + -2n + 2n

Combine like terms: -12n + 2n = -10n
6 + -10n = 4 + -2n + 2n

Combine like terms: -2n + 2n = 0
6 + -10n = 4 + 0
6 + -10n = 4

Add '-6' to each side of the equation.
6 + -6 + -10n = 4 + -6

Combine like terms: 6 + -6 = 0
0 + -10n = 4 + -6
-10n = 4 + -6

Combine like terms: 4 + -6 = -2
-10n = -2

Divide each side by '-10'.
n = 0.2

Simplifying
n = 0.2

See similar equations:

| x=y+1-4 | | (9x-8)+(10x+10)= | | Y=x+1-4 | | 4x^2-6x-10-mx-m=0 | | 2.5+10=1.5+17 | | 5x-2(2x+2)=-6 | | 9b-4=1+6(b+11) | | sqrt(6+x)*sqrt(4-x)=3 | | 10+-2z=-30 | | 11x-5=60 | | 5m-4=3m+12 | | w^3+5w^2+-23w-3= | | -2=-9-2(-2x+1) | | -7f+-31=53 | | X^3-2x+21=0 | | 20+-10c=100 | | 2b+a=5 | | 2,711/9= | | 0.9=0.8+x-0.8x | | (-4x)(-2x^2)= | | x-21=2x+3 | | (w-3)(w^2+8w+1)= | | 7(x+6)=8(x-4) | | t^2+48t=0 | | (4x)=26 | | 7n^7+9n+5= | | 10.4+4= | | -x^2-12-18=0 | | 10/x=25/20 | | 9(s+10)+7=3s-11 | | f(x)=-2-2x | | rainbow+7=fun |

Equations solver categories